Thathbiq al-Taqyim al-Waqi’i bi al-Manhaj al-Dirasi 2013 Fi Ta’lim al-Lughah al-‘Arabiyah - Hanifah, Umi; Mahmudi, Imam (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This study aims to explain how to plan the authentic assessment according to 2013 Curriculum in Arabic teaching, how to apply the authentic assessment according to 2013 Curriculum in Arabic teaching and what problems in applying the authentic assessment according to 2013 Curriculum in Arabic teaching and the solution. Thus, this study is very important for Arabic language teachers in implementing the authentic assessment according to 2013 properly. This study is a qualitative descriptive study. The subjects in this study were Arabic teachers in class XI at State Islamic Senior High schooI 2 Bojonegoro, East Java. Data collection uses observation، interview and documentation techniques. The results showed that the planning of authentic assessment according to curriculum 2013 in Arabic teaching at State Islamic Senior High schooI 2 Bojonegoro was carried out properly. Teachers have used several forms of authentic assessment، such as in cognitive assessment، they use written and oral tests، in affective assessments، they use observation، self-assessment، peer assessment، and journals، in psychomotor assessments they use performance assessments، projects، and portfolios. The problematic of teachers in implementing authentic assessment in Arabic teaching are the teachers find it difficult to develop instruments and determine authentic forms of assessment. The solution to these problems is that the teacher tries to understand the guidelines for authentic assessment and applies the basic form of authentic assessment in teaching.